Alex Rider. scorpia rising - Horowitz, Anthony, 1955- (New York : Puffin Books, 2012)
Alex Rider must once again do battle against the terrorist organization responsible for the death of his parents--Scorpia--when their plot in the Middle East poses a threat to humanity, but this time around the risks are bigger and Alex will not walk away so easily.
Keywords: Terrorism -- Juvenile fiction; Orphans -- Juvenile fiction; Spy stories; Adventure stories; Orphans -- Fiction; Terrorism -- Fiction; Middle East -- Juvenile fiction; London (England) -- Juvenile fiction; England -- Juvenile fiction; Middle East -- Fiction; London (England) -- Fiction; England -- Fiction